Innentitelbild: Ligand Assisted Thermal Atomization of Palladium Clusters: An Inspiring Approach for the Rational Design of Atomically Dispersed Metal Catalysts (Angew. Chem. 16/2023). (24th March 2023) - Wang, Sicong; Ding, Tao; Liu, Tong; Zhu, Yanan; Tao, Zhinan; Pang, Beibei; Liu, Xiaokang; Luo, Qiquan; Sun, Mei; Sheng, Hongting; Zhu, Manzhou; Yao, Tao
Abstract : The low‐temperature conversion of Pd nanoclusters into Pd single atoms with the assistance of Cl ligands is illustrated by Tao Ding, Xiaokang Liu, Manzhou Zhu, Tao Yao et al. in their Research Article (e202218630) . The Pd nanoclusters collapse when coordinated by Cl ligands, thus enabling the transformation to take place at low temperatures (400 °C). This study sheds light on the rational design of atomically dispersed metal catalysts.